PEMANFAATAN DEM-SRTM DAN DEM-NAS SEBAGAI DASAR SIMULASI HUJAN-DEBIT DI DAS KALIWADAS - Sukandi Samatan; Heri Suprapto (Jurnal Ilmiah Desain & Konstruksi, 2023)
The accuracy of flow prediction in a watershed for water resource development is highly dependent on various factors such as the transformation model used, the availability and accuracy of hydrological data and watershed characteristics such as topography, drainage networks, land cover and soil texture. Watershed characteristics are considered as the most dominant determinants in various hydrological analyzes, especially with regard to the data used to compile the watershed model, in this case the Digital Elevatian Model (DEM) data. This study aims to develop a watershed model based on National DEM (DEMNAS) data to estimate daily discharge using the HEC-HMS model and design discharge using the Nakayasu Synthetic Unit Hydrograph (SUH) method. The research was conducted in the Kaliwadas watershed, which is located in Kandang Serang District, Pekalongan Regency, Central Java Province. Kaliwadas River is one of the sub-watersheds with a drainage area of approximately 165.78 km2 which has a good enough potential to supply hydro-based electricity. The performance of the DAS model formed with DEMNAS data is compared with the performance of the watershed model formed with the DEM Shuttle Radar Topography Mission (SRTM) data, where these two DEM data have a resolution of 8 meters and 90 meters, respectively. Performance testing is based on the Root Mean Square Error (RMSE) number of the two predictive flow from the HEC-HMS Model to the observed discharge. The results showed that the estimated discharge of the HEC-HMS Model using the DEMNAS Watershed Model showed slightly better performance than using the SRTM DAS Model, with a RMSE difference of 0.27.